EXPERIMENTAL CONSTRAINTS ON UREILITE PETROGENESIS - Singletary S.; Grove T.L. (My University, 2006)
This experimental study explores the petrogenesis of ureilites by a partial melting/smelting process. Experiments have been performed over temperature (1150-1280 °C), pressure (5-12.5 MPa), and low oxygen fugacity (graphite-CO gas) conditions appropriate for a hypothetical ureilite parent body ~200 km in size. Experimental and modeling results indicate that a partial melting/smelting model of ureilite petrogenesis can explain many of the unique characteristics displayed by this meteorite group. Compositional information preserved in the pigeonite-olivine ureilites was used to estimate the composition of melts in equilibrium with the ureilites. The results of 20 experiments saturated with olivine, pyroxene, metal, and liquid with appropriate ureilite compositions are used to calibrate the phase coefficients and pressure-temperature dependence of the smelting reaction. The calibrated coefficients are used to model the behavior of a hypothetical residue that is experiencing fractional smelting. The residue is initially olivine-rich and smelting progressively depletes the olivine content and enriches the pyroxene and metal contents of the residues. The modeled residue composition at 1260 °C best reproduces the trend of ureilite bulk compositions. The model results also indicate that as a ureilite residue undergoes isothermal decompression smelting over a range of temperatures, Ca/Al values and Cr2O3 contents are enriched at lower temperatures (below ~1240 °C) and tend to decrease at higher temperatures. Therefore, fractional smelting can account for the high Ca/Al and Cr2O3 wt% values observed in ureilites. We propose that ureilites were generated from an olivine-rich, cpx-bearing residue. Smelting began when the residue was partially melted and contained liquid, olivine, and carbon. These residues experienced varying degrees of fractional smelting to produce the compositional variability observed within the pigeonite-bearing ureilites. Variations in mineral composition, modal proportions, and isotopic signatures are best described by heterogeneous accretion of the ureilite parent body followed by minimal and variable degrees of igneous processing. © 2005 Elsevier Inc. All rights reserved.
Keywords: ureilite